Pranciškaus Tičkovskio kolekcijos ir archyvo tyrimas: chronologinis aspektas - (:unkn) unknown (My University, 2018)
Lietuvos mokslų akademijos Vrublevskių bibliotekoje saugomi kunigo Pranciškaus Tičkovskio rankraščiai, knygos, grafikos kūriniai ir ekslibrisai, senienos ir dantiraščiai, taip pat laiškai ir atvirukai, kurie XX a. ketvirtajame dešimtmetyje buvo atiduoti Vrublevskių bibliotekai. Devintajame dešimtmetyje iš nemažos kolekcijos ir asmeninio archyvo dalies, išsaugotos Bibliotekos Rankraščių skyriuje, buvo suformuotas Pranciškaus Tičkovskio fondas (F147). Tačiau kita kolekcijos dalis, apie kurią žinoma iš pavienių spaudinių ir grafikos kūrinių, dar nėra mums pažįstama. Straipsnio tikslas yra aptarti P. Tičkovskio kolekciją, surinktą skirtingais gyvenimo laikotarpiais, atskleisti šios kolekcijos ir archyvo ryšį. Esminiai žodžiai: Lietuvos mokslų akademijos Vrublevskių biblioteka; Pranciškus Tičkovskis; kolekcija; asmeninis archyvas. Keywords: The Wroblewski Library of the Lithuanian Academy of Sciences; Franciszek Tyczkowski; collection; private archive.

The Rare Book Department in the Wroblewski Library of the Lithuanian Academy of Sciences is home to the collection of Father Franciszek Tyczkowski (1891–1982), which features manuscripts, books, graphic art prints, bookplates, a collection of antiquities and a set of unique cuneiform tablets. Father Tyczkowski donated this collection and his personal archive to the Wroblewski Library, which had been founded in the early 20th century and opened to public in 1935. At that point there was not enough time to establish a proper Tyczkowski collection, and the latter was formed only in the eighties based on manuscripts and other documents which had fallen into the holdings of the Manuscript Department. The rest of the collection, whose existense may be deduced from individual publications and art prints, was split among different other collections and so is not always easily recognizable by researchers. Based on archival evidence, the article aims to characterize the Tyczkowski collection amassed and handed over to the library in the period from the second to the fourth decade of the 20th century, according special attention to chronological issues. The article also addresses the relation of this diverse collection to the Tyczkowski archive. Tyczkowski started collecting at a young age. Research shows a particular importance of his archive’s different sub-collections. They are likely tied to different periods in the collector’s life: to his studies at the University of Warsaw, and then, in the third decade, at the Pontifical Biblical Institute; to the St Archangel Michael Church at the Vilnius Bernardine Monastery, where he was rector until the mid-thirties; to the Akmenynė estate (the present Šalčininkai district) owned by the Reniger family and the construction of St. Therese of the Child Jesus Church in the late twenties. Acquired by Tyczkowski over the thirties, his bookplates make a separate sub-collection. Both the latter and a majority of letters addressed to Tyczkowski are a testimony to an active exchange of bookplates he maintained with collectors from Vilnius and Kaunas, from Warsaw and other Polish cities; as well as from Italy, Latvia, Portugal and other countries.
A look into the collection and archive of Franciszek Tyczkowski: a chronological aspect
Moksliniai straipsniai / Scientific articles
Keywords: Lietuvos mokslų akademijos Vrublevskių biblioteka; Pranciškus Tičkovskis